Two-Weighted Estimate for Generalized Fractional Integral and Its Commutator on Generalized Fractional Morrey Spaces (Journal of Mathematical Study, 2023)
The aim of this paper is to establish the mapping properties of generalizedfractional integral $I_ρ$ and its commutator $[b,I_ρ]$ formed by $b∈{\rm BMO}(\mathbb{R}^n)$ and the $I_ρ$ ongeneralized fractional weighted Morrey spaces $\mathcal{L}^{p,η,φ}_ω (\mathbb{R}^n),$ where $φ$ is a positive andnon-decreasing function defined on $(0,∞),$ $η∈(0,n)$ and $p∈[1, \frac{n}{η}).$